SYNTHESIS, CHARACTERISATION & ANTIMICROBIAL STUDIES OF CO(II) & NI(II) COMPLEXES WITH SOME SUBSTITUTED PYRAZOLES DERIVATIVES - MANIKA BARAR, (International Journal of Pharma and Bio Sciences, 2014)
We reported here some new biological important metal- dizole complexes of the type ML2X2 Where M = Ni (II ) and Co (II) , L = 2-( Pyrazol- 1-yl) pyridine (I) , 2- (3,5 – Dimethyl pyrazole -1-yl) 5 methyl pyridine (II) , 2- (3,5- Diphenyl pyrazole-1- yl) pyridine (III) , 2-(3,5- diphenyl pyrazol-1-yl ) 5- methyl pyridine (IV ) and X = Cl. These complexes have been tested against various bacteria such as Staphylococcus aureus, Escheria coli and Pseudomonas aeruginosa. The complexes show significant antimicrobial activity compared to that of parent compound.